Fatigue performance of thermal spray coatings on carbon steel: a review - M. Halmi, M. A.; Harimon, M. A.; Mohd Tobi, L.; Mahmod, M. F. (IAEME Publication, 2019)
This paper contributes to a review of the research of the fatigue behaviour of thermal spray coatings on carbon steel. Previous studies provide the experimental characterization of the fatigue resistance of coated carbon steel. Different coating powders were deposited to a different type of carbon steels. Also, S-N curves were drawn from axial- and rotating bending fatigue test to determine the fatigue strength or fatigue limit of the samples. Thermal spray coatings showed great improvement to the work hardening effect but worsen the fatigue life due to the inclusion of oxide and pores, the presence of stress concentrators, and high microcrack density. Moreover, the effects of the surrounding environment have also resulted in pros and cons towards the fatigue strength. An improvement, however, can be done with the shot peening treatment, which significantly increases the compressive residual stress at interfaces of coating/substrate. The high compressive residual stress could delay the crack nucleation, thus increasing the fatigue life of the coated part.